Swazi youths' attitudes and perceptions concerning adolescent pregnancies and contraception - I S Ziyane; V J Ehlers (AOSIS, 2006)
This study investigated Swazi adolescents' attitudes and perceptions concerning adolescent pregnancies and contraceptive practices in order to help address the continued challenge posed by large numbers of adolescent pregnancies in Swaziland. Opsomming Hierdie studie het Swazi adolessente se houdings en persepsies in verband met adolessente swangerskappe en voorbehoedpraktyke ondersoek om die volgehoue uitdaging van groot getalle adolessente swangerskappe in Swaziland aan te spreek. *Please note: This is a reduced version of the abstract. Please refer to PDF for full text.